An atypical case of ectopic ACTH syndrome in an adolescent boy. Issue 3 (6th May 2020) - Sharma, Shreya; Joshi, Rajesh
Abstract: Ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS) is exceedingly rare in children and scarcely reported. Pancreatic neuroendocrine tumours (NETs) can rarely lead to secretion of ectopic ACTH. A 14-year-old boy presented with hyperpigmentation, hypertension and intermittent abdominal pain, and was diagnosed with endogenous hypercortisolism. An incidental pancreatic mass discovered on routine ultrasonogram (USG) revealed the source of ACTH. He underwent successful excision of the mass with resolution of hypercortisolism. The histopathology revealed a Pancreatic NET and immunohistochemistry was positive for ACTH stain.